2020
DOI: 10.1177/2340944420929711
|View full text |Cite
|
Sign up to set email alerts
|

The microfoundations of organizational ambidexterity: A systematic review of individual ambidexterity through a multilevel framework

Abstract: The analysis of ambidexterity at the individual level may help to open the black box of organizational ambidexterity and to address the microfoundations of the exploration/exploitation dilemma in order to know how it can be achieved. The purpose of this article is to examine the main characteristics, antecedents, and consequences of individual ambidexterity, highlighting several key theoretical and methodological issues. Through a systematic literature review, we synthesize and integrate knowledge about indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(85 citation statements)
references
References 100 publications
(298 reference statements)
2
53
1
1
Order By: Relevance
“…A systematic literature review was used since it is suggested as an appropriate technique for determining research gaps in current literature and providing future search directions (Hao et al, 2019). Thus, the procedures for the systematic literature review were conducted by considering the suggestions developed by Palmatier et al (2018), Okoli (2015), andTranfield et al (2003), and previous review studies (Keupp & Gassmann, 2009;Paul et al, 2017;Pertusa-Ortega et al, 2020) and theory-based review studies (Gilal et al, 2019(Gilal et al, , 2021. This study followed the six major steps, which are topic formulation, study design, sampling, data collection, analysis, and reporting (Palmatier et al, 2018).…”
Section: Me Thodologymentioning
confidence: 99%
See 3 more Smart Citations
“…A systematic literature review was used since it is suggested as an appropriate technique for determining research gaps in current literature and providing future search directions (Hao et al, 2019). Thus, the procedures for the systematic literature review were conducted by considering the suggestions developed by Palmatier et al (2018), Okoli (2015), andTranfield et al (2003), and previous review studies (Keupp & Gassmann, 2009;Paul et al, 2017;Pertusa-Ortega et al, 2020) and theory-based review studies (Gilal et al, 2019(Gilal et al, , 2021. This study followed the six major steps, which are topic formulation, study design, sampling, data collection, analysis, and reporting (Palmatier et al, 2018).…”
Section: Me Thodologymentioning
confidence: 99%
“…This study followed the six major steps, which are topic formulation, study design, sampling, data collection, analysis, and reporting (Palmatier et al, 2018). Considering the systematic literature review methodology (Gilal et al, 2019;Keupp & Gassmann, 2009;Okoli, 2015;Paul & Criado, 2020;Paul et al, 2017;Pertusa-Ortega et al, 2020;Rebouças & Soares, 2020), the domain of this review is the academic articles published in the journals indexed in Web of Science and Scopus, which were chosen to ensure a complete coverage of research related to the TCV across various journals and to guarantee the quality of the selected articles. Article was selected as the document type for the review because it covers verified knowledge, has the highest impact power in the field, and depicts the research area that shows the research attention and resources with solid perspective (Keupp & Gassmann, 2009).…”
Section: Me Thodologymentioning
confidence: 99%
See 2 more Smart Citations
“…Second, constructs related to how individuals experience and respond to role‐based or psychological conflicts, tensions, and paradoxes may moderate the effects of different conceptualizations of middle power on various outcomes. For example, individuals who are higher (vs. lower) in individual ambidexterity (Bledow et al., 2009; Martin et al., 2019; Papachroni & Heracleous, 2020; Pertusa‐Ortega et al., 2020) or have a stronger (vs. weaker) paradox mindset (Miron‐Spektor et al., 2018; see also Kleiman & Enisman's,2018 perspective on “conflict mindsets”) may be better equipped to navigate the challenges associated with occupying a middle‐power role and/or experiencing fluctuating power states. Similarly, benefits may accrue to middle‐power individuals who endorse a middle‐ground approach to resolving paradoxes, which involves “taking a midway position that acknowledges each of the two opposing elements or positions in a paradox to moderate levels, such that parts of these opposing aspects are preserved” (Leung et al., 2018, p. 445).…”
Section: Future Directionsmentioning
confidence: 99%